Long-term structural and symptomatic effects of intra-articular sprifermin in patients with knee osteoarthritis: 5-year results from the FORWARD study. Issue 8 (7th May 2021) - Eckstein, Felix; Hochberg, Marc C; Guehring, Hans; Moreau, Flavie; Ona, Victor; Bihlet, Asger Reinstrup; Byrjalsen, Inger; Andersen, Jeppe Ragnar; Daelken, Benjamin; Guenther, Oliver; Ladel, Christoph; Michaelis, Martin; et al.
Abstract : Objective: The FORWARD (FGF-18 Osteoarthritis Randomized Trial with Administration of Repeated Doses) trial assessed efficacy and safety of the potential disease-modifying osteoarthritis drug (DMOAD) sprifermin in patients with knee osteoarthritis. Here, we report 5-year efficacy and safety results. Methods: Patients were randomised to intra-articular sprifermin 100 µg or 30 µg every 6 months (q6mo) or 12 months, or placebo, for 18 months. The primary analysis was at year 2, with follow-up at years 3, 4 and 5. Additional post hoc exploratory analyses were conducted in patients with baseline minimum radiographic joint space width 1.5–3.5 mm and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain 40–90, a subgroup at risk (SAR) of progression. Results: 378 (69%) patients completed the 5-year follow-up. A significant dose-response in total femorotibial joint cartilage thickness with sprifermin (trend test, p<0.001) and a 0.05 mm mean difference with sprifermin 100 µg q6mo versus placebo (95% CI 0.00 to 0.10; p=0.015) were sustained to year 5. WOMAC pain scores improved 50% from baseline in all groups. No patient in the 100 µg q6mo group had replacement of the treated knee. 96%–98% of patients receiving sprifermin and 98% placebo reported adverse events, most were mild or moderate and deemed unrelated to treatment. Adverse event-related study withdrawals were <10%. Differentiation in WOMAC pain between sprifermin 100 µg q6mo and placebo in the SAR (n=161) at year 3 was maintained to year 5 (−10.08; 95% CI −25.68 to 5.53). Conclusion: In the longest DMOAD trial reported to date, sprifermin maintained long-term structural modification of articular cartilage over 3.5 years post-treatment. Potential translation to clinical benefit was observed in the SAR. Trial registration number: NCT01919164